2019
DOI: 10.1016/j.brs.2018.12.233
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow-Up Study with non-invasive brain stimulation (NBS) (rTMS and tDCS) in Parkinson’s disease (PD). Strong Age Dependency in the Effect of NBS

Abstract: Background: Transcranial magnetic stimulation (rTMS) may influence the progression of PD compared with levodopa. The long term mind modification effect of repeated rTMS and tDCS is not known, nor are the predictors for the effect of NBS. Objective/hypothesis: We hypothesized that the regularly repeated rTMS would decrease the development of PD. Later, the treatment protocol was completed with transcranial direct current stimulation (tDCS), supposing that there is an add-on effect. NBS may differently influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…A large majority of the studies presented describe the most relevant characteristics for the characterization of participants in the baseline, however, they do not address how they could interfere in the interpretation of the results. A long-term follow-up study (Málly et al, 2018) of the use of NIBS (rTMS and tDCS), showed that the therapy is able to slow the progression of the disease, but that age is the main predictor of its effect. In other clinical populations such as stroke, these predictors of response may be related to the severity of symptoms, the size and location of the lesions, the etiology of the stroke and the time from symptom onset to intervention (Ovadia-Caro et al, 2019).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…A large majority of the studies presented describe the most relevant characteristics for the characterization of participants in the baseline, however, they do not address how they could interfere in the interpretation of the results. A long-term follow-up study (Málly et al, 2018) of the use of NIBS (rTMS and tDCS), showed that the therapy is able to slow the progression of the disease, but that age is the main predictor of its effect. In other clinical populations such as stroke, these predictors of response may be related to the severity of symptoms, the size and location of the lesions, the etiology of the stroke and the time from symptom onset to intervention (Ovadia-Caro et al, 2019).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…This combinatory approach has been proved to be more effective than either protocol alone in achieving optimal motor cortical plasticity based on metaplasticity effects, [4] as well as in driving clinical gains. [5][6][7] Further, studies have demonstrated that autonomic cardiovascular control through modulation of neurocardiac regulation could be influenced by electrical or magnetic stimulation. [8,9] While the motor cortical and clinical effects of dual stimulation are evident, [5][6][7] its effect on neurocardiac regulation which might be related to changes in excitability measures has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Further, studies have demonstrated that autonomic cardiovascular control through modulation of neurocardiac regulation could be influenced by electrical or magnetic stimulation. [8,9] While the motor cortical and clinical effects of dual stimulation are evident, [5][6][7] its effect on neurocardiac regulation which might be related to changes in excitability measures has not been well studied. We designed the current study with objectives of investigating the effects of priming rTMS with tDCS on cardiac autonomic control as assessed by heart rate variability (HRV) and motor cortical excitability measures using TMS.…”
Section: Introductionmentioning
confidence: 99%